2021
DOI: 10.1044/2020_ajslp-20-00102
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Augmented Input Interventions and Exploratory Analysis of Moderators

Abstract: Purpose Augmented input is the act of concurrently modeling language verbally and on a communication device, and is one strategy for teaching individuals to effectively use aided modes of communication. The purpose of this literature review is to assess the efficacy of augmented input for increasing communication and to identify intervention components, participant characteristics, and instructional contexts related to therapeutic outcomes. Method We do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 48 publications
2
2
1
Order By: Relevance
“…Our findings were similar to those of prior reviews and meta-analyses. For instance, prior work found substantial heterogeneity in characteristics of participants and in instruction in a range of communicative functions (Chazen et al, 2021;Ganz et al, 2017;Iacono et al, 2016;Logan et al, 2017). Similar to other reviews, we found that instruction focused on behavior regulation more often than more socially advanced communicative functions (Holyfield et al, 2017;Morin et al, 2018), although those reviews were limited to less expansive populations or AAC modes.…”
Section: Results In Relation To Prior Reviews and Meta-analysessupporting
confidence: 84%
“…Our findings were similar to those of prior reviews and meta-analyses. For instance, prior work found substantial heterogeneity in characteristics of participants and in instruction in a range of communicative functions (Chazen et al, 2021;Ganz et al, 2017;Iacono et al, 2016;Logan et al, 2017). Similar to other reviews, we found that instruction focused on behavior regulation more often than more socially advanced communicative functions (Holyfield et al, 2017;Morin et al, 2018), although those reviews were limited to less expansive populations or AAC modes.…”
Section: Results In Relation To Prior Reviews and Meta-analysessupporting
confidence: 84%
“…SCARF Q&R scores are calculated by averaging rigor scores and quality scores and double-weighting rigor; the range of possible scores is 0 to 4. We identified scores above 2.0 indicating high-quality studies and scores of 1.8 as having adequate quality for interpreting outcomes; these values are consistent with previous research (Chazin et al, 2021; Zimmerman et al, 2017). Outcomes were evaluated via the SCARF based on visual analysis, with a score of 0 indicating no positive effects or detrimental behavior changes, scores of 1 to 2 indicating inconsistent effects, and scores of 3 to 4 indicating consistent positive effects.…”
Section: Methodssupporting
confidence: 86%
“…Our findings were similar to those of prior reviews and meta-analyses. For instance, prior work found substantial heterogeneity in characteristics of participants and in instruction in a range of communicative functions (Chazen et al, 2021;Ganz, et al, 2017;Lacono et al, 2016;and Logan et al, 2017). However, some reviews found that instruction focused on behavior regulation more often than more socially advanced communicative functions (Holyfield et al, 2017;Morin, et al, 2018), in contrast to what we found, although those reviews were limited to less expansive populations or AAC modes.…”
Section: Results In Relation To Prior Reviews and Meta-analysescontrasting
confidence: 64%